Principles of Statutory Duty and Fiduciary Duty in The Responsibility of The Bankruptcy Curator - Raden Besse Kartoningrat; Edi Krisharyanto (Media Iuris, 2023)
AbstractThe curator is a subject of Bankruptcy Law who has complete authority and responsibility for managing and resolving the bankruptcy estate. Curators are required to have integrity and are prohibited from having conflicts of interest with their duties and authorities. The issue raised in this study is the application of the principles of statutory duty and fiduciary duty in the responsibility of the bankruptcy curator. This study aims to identify, understand, and analyze bankruptcy law regarding the curator’s responsibility based on the principles of statutory duty and fiduciary duty. This study employed a normative method by examining the consideration materials to conclude. The results of the analysis in this study indicate that in carrying out the duties of managing and settling, the curator must comply with the principles of statutory duty and fiduciary duty as regulated in Law Number 37 of 2004 on Bankruptcy and Postponement of Debt Payment Obligations and the code of ethics of the curator profession. The curator’s actions that can harm the parties, whether creditors or bankrupt debtors, can be personally accounted for outside the bankruptcy estate by imposing civil, criminal, or administrative sanctions. Keywords: Halal Tourist; Additional Service; Local Economy.